OCCUPACIONAL EXPOSURE TO NON IONIZING RADIATION FROM MEDICAL PROCEDURES - Valdivia Maldonado, Pedro Oswaldo (2021)
Occupational exposure levels for Magnetic Equipment, Surgical and Therapeutics Diathermy were evaluated. No damage was observed, nonetheless workers still show concern; exposure levels are lower than the ICNIRP limits. Records should be established, to continue long-term research .